2016
DOI: 10.1038/srep36993
|View full text |Cite
|
Sign up to set email alerts
|

mRNA changes in nucleus accumbens related to methamphetamine addiction in mice

Abstract: Methamphetamine (METH) is a highly addictive psychostimulant that elicits aberrant changes in the expression of microRNAs (miRNAs) and long non-coding RNAs (lncRNAs) in the nucleus accumbens of mice, indicating a potential role of METH in post-transcriptional regulations. To decipher the potential consequences of these post-transcriptional regulations in response to METH, we performed strand-specific RNA sequencing (ssRNA-Seq) to identify alterations in mRNA expression and their alternative splicing in the nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 59 publications
2
30
0
Order By: Relevance
“…However, RNA-seq alone may not provide pragmatic results in a multigenic disease, such as drug addiction, because of extensive raw data; therefore, data management and computational screening are needed. The integration of bioinformatics and biological network analysis enables RNA-seq to define specific groups of genes that are related to drug addiction behaviour 22 . Recent advances in bioinformatics facilitate analysis of complex signalling transduction in cells through investigation of multiple types of interaction networks 23 .…”
Section: Introductionmentioning
confidence: 99%
“…However, RNA-seq alone may not provide pragmatic results in a multigenic disease, such as drug addiction, because of extensive raw data; therefore, data management and computational screening are needed. The integration of bioinformatics and biological network analysis enables RNA-seq to define specific groups of genes that are related to drug addiction behaviour 22 . Recent advances in bioinformatics facilitate analysis of complex signalling transduction in cells through investigation of multiple types of interaction networks 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Prior exposure to MA can potentiate the effects of MA re-exposure on behavior (Jing et al 2014) and impact DA concentration in the striatum (McFadden et al 2015;Lominac et al 2014). H1 +/mice could have disrupted transcriptional regulation of key genes involved in psychostimulant sensitization and physical dependence (Cates et al 2018;Zhu et al 2016;Piechota et al 2012), resulting in effects on reward sensitivity and magnitude at the time of re-exposure that depend on prior exposure. The effects of prior MA exposure on reinforcement depends on several factors, including dose, length of exposure, and latency to re-exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Our work describes a critical role for Tmod2 in drug-induced behavioral sensitization and voluntary drug intake. Tmod2 has been weakly linked to risky drug use in humans and its gene expression and protein levels are dynamic upon drug exposure in animal models [46][47][48][49][50][51][52][53] . We provide behavioral data that Tmod2…”
Section: Discussionmentioning
confidence: 99%
“…In human candidate gene studies, Gelernter and colleagues showed that Tmod2 is associated with drug-dependent risk-taking behavior and proposed TMOD2-mediated remodeling of brain areas regulating sexual function and behavior 46 . In several transcriptomics and proteomics studies, Tmod2 mRNA and protein levels are differentially modulated following repeated methamphetamine [47][48][49] , alcohol 50 , cocaine 51 , or morphine 52 administration in animal models. These studies led a meta-analysis to suggest Tmod2 is an addiction candidate gene 53 .…”
Section: Introductionmentioning
confidence: 99%